بروتوكول التحويل الشجري الديناميكي DTR في شبكات الحساسات اللاسلكية المعتمدة على تقنية ذكبي (Latakia University Journal -Engineering Sciences Series, 2018)
In many wireless sensor network applications like forest fire detection and environment monitoring, battery powered sensors are often randomly distributed in monitoring area, and data packets are usually sent from those sensors toward network's main coordinator which acts as a gateway to the monitoring center. Considering such network routing requirements, and the limited sensor energy, we proposed our Dynamic Tree Routing Protocol (DTR), which is an improved version of Modified Zigbee Hierarchical Tree Routing Protocol (MZBR), this protocol dynamically distributes traffic to coordinator in each hop according to specific quality factor depends on the depth, Link Quality Indicator (LQI), and the remaining energy of receiving sensor. The simulation results obtained from Network Simulator Version 2 (NS2) showed better distribution of energy consumption and improvement in network lifetime, while keeping good packet delivery ratio and end to end delay compared with On Demand Distance Vector AODV and Modified Zigbee Hierarchical Tree Routing  MZBR Protocols. في كثير من تطبيقات شبكات الحساسات اللاسلكية كتطبيقات كشف حرائق الغابات ومراقبة البيئة، يتم توزيع الحساسات اللاسلكية المعتمدة على البطاريات عشوائيا في منطقة المراقبة، وغالبا ما يتم ارسال البيانات من هذه الحساسات باتجاه منسق الشبكة الرئيسي الذي يعمل كبوابة عبور الى مركز المراقبة. بأخذ متطلبات التحويل لمثل هذه الشبكات بالحسبان، ومحدودية طاقة الحساسات، قمنا بتطوير بروتوكول التحويل الشجري الديناميكي (DTR) والذي هو تحديث لبروتوكول التحويل الشجري المعدل في ذكبي (MZBR)، يقوم هذا البروتوكول بشكل ديناميكي بتوزيع الحمل المتجه الى منسق الشبكة في كل قفزة بالاعتماد على معامل جودة محدد يعتمد على العمق، مؤشر جودة الوصلة (LQI)، وعلى الطاقة المتبقية في الحساس المستقبل. أظهرت النتائج التي حصلنا عليها باستخدام محاكي الشبكات الإصدار الثاني (NS2) توزيع أفضل لاستهلاك الطاقة وزيادة في زمن حياة الشبكة، مع الاحتفاظ بمعدل تسليم بيانات وزمن تأخير جيد مقارنة بالبروتوكول AODV وبروتوكول التحويل الشجري المعدل في ذكبي.